INFLUENCE OF STAKEHOLDERS' CONTRIBUTION ON SECURITY MANAGEMENT OUTCOMES IN PUBLIC SECONDARY SCHOOLS IN MANDERA COUNTY, KENYA - Daud, Abdi; Thinguri, Ruth; Mugwe, Mary (African Journal of Education and Practice, 2022)
Purpose: There is a current anxiety on the increasing occurrences of tragedies in secondary schools in Kenya. This makes it essential to explore the stakeholders' contribution in terms of security management outcomes. The aim of this research was to explore the influence of stakeholders' contribution on security management outcomes in public secondary schools in Mandera County, Kenya. Methodology: Theories guiding the study were the Stakeholders' and the Securitization. The study used mixed methodology and the concurrent triangulation design. The targeted population was 381 participants and involved principals and teachers. Questionnaires were used for teachers while interviews were used for principals. Quantitative data were analyzed in descriptive statistics and presented in tables, frequencies and percentages. Qualitative data were analyzed by thematically in narrative forms and verbatim citations. Two levels of analysis were employed namely: descriptive and thematic. Findings: From the research findings, it was concluded that there was good participation of every stakeholder following the indicators that were put in place. It was seen that there was need for the boards of management to go deeper into their involvement and make sure that the school communities were seeing them in action. Unique Contribution to Theory, Policy and Practice: The stakeholders' and the securitization theories were utilized to prepare and alert schools for disasters consecutively hence contributing to the issues in the study. The study established that there was meaningful contribution from the stakeholders which was commendable. It was concluded that more efforts from the boards of management be put on stakeholders' contribution. The theories were validated in that there was sensitization to stakeholders and the need to prepare in advance for disasters in schools.